1968 - Eine Wahrnehmungsrevolution? Horizont-Verschiebungen des Politischen in den 1960er und 1970er Jahren - Gilcher-Holtey, Ingrid (Zeitgeschichte im Gespräch, 2013)
Was the 1968 movement a cultural success but a political failure? The six studies compiled in this volume probe the structural changes and shifting boundaries of political life in the 1960s and 1970s to assess the impact of the 1968 movement. Among other phenomena, they examine the theater as a potential medium for staging politics, and television as a vehicle in social protest.